2009
DOI: 10.1016/j.bbabio.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast fluorescence study on the location and mechanism of non-photochemical quenching in diatoms

Abstract: The diatom algae, responsible for at least a quarter of the global photosynthetic carbon assimilation in the oceans, are capable of switching on rapid and efficient photoprotection, which helps them cope with the large fluctuations of light intensity in the moving waters. The enhanced dissipation of excess excitation energy becomes visible as non-photochemical quenching (NPQ) of chlorophyll a fluorescence. Intact cells of the diatoms Cyclotella meneghiniana and Phaeodactylum tricornutum, which show different N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 32 publications
11
116
2
Order By: Relevance
“…In addition, the FCP composition of the antenna varied if the algae were grown under LL or HL conditions [31] . Heterogeneity of FCPs can also be seen in the ultrafast fluorescence decay kinetics [32], which showed that two different pools of FCPs are responsible for the generation of steady-state non-photochemical fluorescence quenching (NPQ) in the diatoms P. tricornutum and C. meneghiniana. One pool of FCPs, detached from the photosystems, forms a fluorescence-quenching site, whereas the second quenching site consists of FCPs that remain in contact with the PSII core complex [32].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the FCP composition of the antenna varied if the algae were grown under LL or HL conditions [31] . Heterogeneity of FCPs can also be seen in the ultrafast fluorescence decay kinetics [32], which showed that two different pools of FCPs are responsible for the generation of steady-state non-photochemical fluorescence quenching (NPQ) in the diatoms P. tricornutum and C. meneghiniana. One pool of FCPs, detached from the photosystems, forms a fluorescence-quenching site, whereas the second quenching site consists of FCPs that remain in contact with the PSII core complex [32].…”
Section: Resultsmentioning
confidence: 99%
“…qNf could be related to a fast conformational change occurring within the thylakoid membranes at the start of the relaxation process. The different (very fast in their creation) qN components could be localized on PSII attached or detached LHCs [58]. The former would be related to the qN enhancing mechanism(s), whereas qNs could be heterogeneous from the mechanistic point of view and related to photoinhibition and/or partial dissipation of the pH gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Nonphotochemical quenching (NPQ) is an additional mechanism that decreases the variable fluorescence of PSII, and all water samples were dark-adapted for 30 min prior to PAM analysis in order to control for this. However, there is emerging evidence suggesting that, in certain diatom species, low levels of PAR are required for complete relaxation of NPQ (Grouneva et al 2008Miloslavina et al 2009). Given that these diatom species were not present in any of the phytoplankton communities we examined, and that diatoms were a very minor component of the phytoplankton in the two lakes that exhibited the greatest losses of F V : F M under irradiance (Brandy and Fawn lakes), it seems unlikely that residual NPQ appreciably affected our measurement of F V : F M .…”
Section: Discussionmentioning
confidence: 99%